Evaluation of nutrient response in different rice (Oryza sativa) varieties - Saha, T.; Pal, S.; Paul, T. (Annals of Agricultural Research, 2016)
A field experiment was conducted during rainy (kharif) season of 2011 at Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal to evaluate the response of nutrient levels on growth and yield of rice varieties. Regarding the varietal effect, maximum grain yield was obtained from hybrid Proagro 6444 (6.57 t/ha) and minimum from high yielding variety Sumo (4.09 t/ha).Among the high yielding varieties, Sourabh showed better grain yield (4.78 t/ha). Hybrid Proagro 6444 was found with maximum numerical value in all growth and yield parameters viz. plant height, number of tillers/hill, dry matter accumulation, panicles/m2, filled grains/panicle and test weight. Application of 100% RDF performed better followed by 75% RDF + 25% FYM among different nutrient levels.